2016
DOI: 10.4269/ajtmh.16-0374
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Outcome of Acute Liver Failure Caused by Dengue in a Hospital for Tropical Diseases, Thailand

Abstract: Abstract. Acute liver failure is an atypical manifestation of dengue with a high mortality. We performed a retrospective cohort study at the Hospital for Tropical Diseases, Bangkok, Thailand. In total, 1,926 patients with serologically confirmed dengue were enrolled in the study from 2011 to 2015. Of these, six patients presented with acute liver failure, four died, and two survived. The incidence of dengue-associated acute liver failure was 0.31%. Dengue-associated acute liver failure was most common among yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 25 publications
(37 reference statements)
0
37
0
Order By: Relevance
“…The main purpose here was to identify whether these samples presented an environment which is consistent with a DAMP-mediated response. Based on the fact that the liver is one of the main organs affected by dengue 35 38 and that lungs and heart are also important sites involved with the severe disease 13 , 37 , 39 41 , samples from all these three organs were considered.…”
Section: Resultsmentioning
confidence: 99%
“…The main purpose here was to identify whether these samples presented an environment which is consistent with a DAMP-mediated response. Based on the fact that the liver is one of the main organs affected by dengue 35 38 and that lungs and heart are also important sites involved with the severe disease 13 , 37 , 39 41 , samples from all these three organs were considered.…”
Section: Resultsmentioning
confidence: 99%
“…The three largest experiences, that studied liver involvement in patients with DF and included more than 3,500 patients, did not find any patient of ALF [ 7 11 18 ]. A recent large retrospective study of 1,926 patients revealed a low (0.31%) incidence rate of ALF in patients with DF [ 8 ]. Over representation of dengue related ALF in few series may be because of undiagnosed co-infection with hepatotropic viruses that could cause ALF or factors related to virulence of the virus involved in a given study.…”
Section: Discussionmentioning
confidence: 99%
“…Liver injury (LI) in patients with DENV infection is common and several hypotheses have been proposed to explain the mechanism of LI [ 5 ]. Severity of LI ranges from asymptomatic mild elevation of serum levels of aminotransferase to life-threatening acute liver failure (ALF) [ 6 7 8 ]. The majority of data on LI in DENV infection is from the adult population.…”
Section: Introductionmentioning
confidence: 99%
“…In the December issue of the Journal, Kye Mon and others describe liver-related complications among 1,926 patients with serologically confirmed dengue infection in Thailand 1. Although the study found only six individuals with acute liver failure, it serves to emphasize how lethal this complication can be.…”
mentioning
confidence: 99%